Transformasi Manajemen Pembelajaran Keaksaraan Fungsional pada Budaya Tari di Kabupaten Konawe Kepulauan - Rasid, Rasid; Ririk, Ririk; Rahma, Rahma; Nasir, Nasir (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2023)
Functional literacy learning includes reading, writing, counting and communicating using Indonesian language that is transformed into the application of dance culture. The purpose of the research is to know the impact of functional literacy learning and its application to the culture of molihi dilaesare dance, motosau molihi dance, dance lense mentoka and kalapea lense dance. The Research Method uses evaluation studies aimed at knowing the impact of functional literacy learning and its transformation in culture. The results stated that functional literacy learning can increase the interest in reading, writing, counting and communicating using Indonesian language transformed into dance culture in Konawe Islands Regency.